The Financial Architecture of Systemic Ecocide and Genocide: Investigating Systemic Criminality and Institutional Failure in Flanders - Priels, Koenraad (University of Darussalam Gontor Press, 2025)
The global financial architecture proves to be a fundamental systemic driver of the currently escalating planetary polycrisis, causing enormous systemic risk by financial instability, economical inefficiency, increasing social inequalities, ecological overshoot and geopolitical tensions. This paper presents a comprehensive analysis of systemic criminality and institutional failure in Flanders, focusing on the global banking system's role in perpetuating systemic ecocide and genocide. Drawing on empirical evidence from Werner's research on bank money creation, Gauvin & Dominguez's mathematical demonstration of monetary system instability and documented regulatory failures, we expose a pattern of institutional protection mechanisms in Flemish regulatory bodies and academic institutions. The paper culminates in a groundbreaking legal complaint filed with the Belgian Public Prosecutor, invoking the new Belgian Ecocide Law to challenge the current financial system's legality. This research demonstrates how Flemish institutions actively perpetuate a criminal system that generates approximately €15 trillion in annual interest payments globally, forcing 3.3 billion people to live in countries spending more on interest than education.